Transformation of Digital Philanthropy Ecosystem: Effectiveness Analysis of Stock Waqf Management Based on Motion Trade Application - M. Syarifuddin Syarifuddin; Taufiqur Rahman (Zamzami Scholar Publishing, 2026)
This study examines the effectiveness of stock waqf management at PT MNC Sekuritas through the Motion Trade application, addressing the critical need for digital transformation in Islamic social finance. Using a qualitative case study design, the research explores how fintech bridges the gap between capital market activities and philanthropic obligations. Data were collected through in-depth interviews with management and investors, supported by empirical documentation of fund distribution. Applying the POAC (Planning, Organizing, Actuating, Controlling) framework, the findings demonstrate that Motion Trade simplifies the waqf mechanism into a seamless digital journey, ensuring systemic sharia compliance. The strategic partnership with certified nazhir institutions facilitates efficient Planning and Organizing, while the Actuating function is visibly evidenced by the rapid mobilization of funds for Gaza humanitarian relief and local orphan support programs. Furthermore, digital audit trails ensure rigorous control and investor trust. The study concludes that this ecosystem effectively democratizes productive waqf, proving that the convergence of technology and management principles transforms stock assets into sustainable social impact, validating the “Holistic Wealth Cycle” in the digital.